Peran Silek Tarlak dalam Acara Manjalang Niniak Mamak di Nagari Sialang Gaung Kecamatan Koto Baru Kabupaten Dharmasraya - Desmita, Dina; Desfiarni, Desfiarni (TSAQOFAH, 2025)
The Manjalang Niniak Mamak tradition is a vital part of Minangkabau culture, rich in kinship values and reverence for elders. One of the prominent cultural elements in this ceremony is Silek Tarlak, a traditional martial art that carries not only aesthetic value but also deep social and cultural significance. This study aims to describe and analyze the role of Silek Tarlak in the Manjalang Niniak Mamak ceremony in Nagari Sialang Gaung, Koto Baru District, Dharmasraya Regency. A descriptive qualitative method was used, focusing on the performance of Silek Tarlak within the traditional event. Data were collected through observation, interviews, literature review, and documentation, and analyzed through stages of data collection, description, identification, and conclusion drawing. The results show that Silek Tarlak holds both symbolic and social roles in the ceremony. It serves to strengthen kinship ties between nephews and maternal uncles (niniak mamak), convey apologies, and honor traditional elders. Additionally, it acts as a symbolic form of protection for the extended family and the community, while also serving as entertainment that enlivens the ceremonial atmosphere. Silek Tarlak embodies moral, aesthetic, educational, and customary values, and fulfills functions such as emotional expression, entertainment, aesthetic enjoyment, social norms, communication, and cultural transmission. Movements such as Gerak Sambah, Gerak Gayuang, Gerak Popek/Tebasan, and Gerak Tumbuak reflect the deep philosophical and cultural meanings embedded in Minangkabau tradition.